Bull Sperm Motility Measurement Improvement Using Sperm Head Direction Angle - Akbar Akbar; Eros Sukmawati; Dwi Utami; Muhammad Nuriyadi; Iwan Awaludin; Priyanto Hidayatullah (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
It is well known that sperm motility is the most important parameter in measuring sperm quality. Sperm motility can be measured manually by a medical veterinarian or using Computer Aided Sperm Analysis (CASA) system. Measuring bull sperm motility manually is the most popular method nevertheless it has major drawbacks which are subjective and high variability. CASA gives consistent results, hence it is an expensive system. Therefore, an alternative method is required. In this paper, a method to measure bull sperm motility was proposed, It was using ellipse detection and sperm head direction angle. The video samples were taken using a digital microscope. Compared with the manual assessment by medical veterinarians, the proposed method gave the average absolute margin of 5.16% which surpassed the previous method which gave 10.69%.